Intervention of Bacterial Leaf Streak of Wheat Through Neem Mediated Copper and Zinc Hybrid Nanoparticles (Journal of Agriculture and Biology, 2025)
Bacterial leaf streak (BLS), caused by Xanthomonas translucens pv. undulosa, is a significant disease affecting wheat crops, leading to considerable yield loss globally. In response to this, green-synthesized nanoparticles offer a promising alternative to traditional chemical treatments, providing both disease management and environmental sustainability. The study evaluated the effectiveness of green-synthesized nanoparticles, including Copper (Cu), Zinc (Zn), and their combination (Cu+Zn), in controlling bacterial leaf streak (BLS) in wheat. A greenhouse trial was conducted using a Completely Randomized Design (CRD) with three replicates for each treatment and nanoparticle concentration (0.25%, 0.50%, and 0.75%). The findings revealed that Cu+Zn nanoparticles achieved the highest reduction in disease incidence (20.5%), followed by Zn nanoparticles (25.6%) and Cu nanoparticles (28.7%) compared to the untreated control. Similarly, a field experiment designed as a Randomized Complete Block Design (RCBD) with three replicates per treatment supported these results. Cu+Zn nanoparticles reduced disease incidence to 23.8%, while Zn nanoparticles and Cu nanoparticles showed reductions of 27.9% and 31.2%, respectively. These findings highlight the potential of neem-mediated copper-zinc hybrid nanoparticles as an effective and environmentally friendly approach for managing bacterial leaf streak in wheat, offering a promising alternative to chemical pesticides.